Paris Conservatoire and Development of Violin Performance - Polina B. Podmazova (Современные проблемы музыкознания)
The opening of the Paris Conservatoire in 1795 played a huge role in the 19th century development of French and wider European performing arts. The article discusses the uniqueness of violin education in the 18th century France and identifies the reasons for the emergence of the world's first educational institution that provided free tuition to all its students regardless of their social background. The article is supplemented with the Russian language translation of the law on the establishment of Paris Conservatoire and a list of its first professors. The article provides a detailed analysis of the initial stage in the development of violin training associated with the names of such famous French violinists as Pierre Gaviniès, Rodolphe Kreutzer, Pierre Rode, and Pierre Baillot. Their wellcoordinated methodological efforts and commitment to common aesthetic ideals encouraged the development of a very powerful violin school that left the rest of Europe behind. The Paris Conservatoire concentrated the best of the country’s artistic potential, thus shaping the musical landscape of France. It also served as a role model for other secular educational institutions located in Europe’s major musical centers.